2022
DOI: 10.1186/s12876-022-02118-y
|View full text |Cite
|
Sign up to set email alerts
|

Overlap between irritable bowel syndrome and common gastrointestinal diagnoses: a retrospective cohort study of 29,553 outpatients in Germany

Abstract: Background Irritable bowel syndrome (IBS) represents the most common functional disorder of the gastrointestinal tract. Many patients with IBS display complex gastrointestinal (GI) symptoms leading to overlapping diagnosis of IBS and other GI diseases in many patients. Methods Using the Disease Analyzer database (IQVIA) featuring patients treated within 2010 and 2019 within 1240 general practices in Germany, we analyzed the prevalence of common GI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…Meanwhile, duodenitis and other components of erosive gastritis, such as raised erosion and depressive erosion, were also significantly associated with IBS. Consistent with our results, Loosen et al reported that the most common overlapping GI diagnoses with IBS are intestinal infectious diseases, gastritis/duodenitis, esophageal diseases, FD, and other diseases of the stomach and duodenum in subjects with IBS using the disease analyzer database in Germany [ 26 ]. There are reports demonstrating the dysbiosis of mucosa-associated microbiota in duodenum in subjects with IBS [ 27 , 28 ], suggesting that altered duodenal microbiota can be one of the causes of duodenitis in subjects with IBS.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, duodenitis and other components of erosive gastritis, such as raised erosion and depressive erosion, were also significantly associated with IBS. Consistent with our results, Loosen et al reported that the most common overlapping GI diagnoses with IBS are intestinal infectious diseases, gastritis/duodenitis, esophageal diseases, FD, and other diseases of the stomach and duodenum in subjects with IBS using the disease analyzer database in Germany [ 26 ]. There are reports demonstrating the dysbiosis of mucosa-associated microbiota in duodenum in subjects with IBS [ 27 , 28 ], suggesting that altered duodenal microbiota can be one of the causes of duodenitis in subjects with IBS.…”
Section: Discussionsupporting
confidence: 92%
“…Nesse caso, o tratamento mais eficaz é o acompanhamento psicológico, pois o estresse é visto como causador principal dessas doenças, principalmente dos distúrbios esofágicos. (Loosen et al, 2022) (Nedelcut et al,2018) De modo geral, conclui-se que existe uma relação significativa entre SII, doenças alérgicas, ansiedade e depressão.…”
Section: Discussionunclassified
“…Earlier research has demonstrated that the panel of German practices represented in the Disease Analyzer database is an accurate reflection of both GPs and specialty practices in Germany [ 19 ]. Notably, this database has been previously employed in studies concentrating on gastrointestinal disorders [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%